Pengembangan Model Kemitraan Closed Loop Beras Organik Melalui Fasilitasi Petani Sanggar Rojolele di Desa Delanggu - Puji Harsono; Dwiningtyas Padmaningrum; Supriyono Supriyono (PRIMA: Journal of Community Empowering and Services, 2025)
Developing a Closed Loop Partnership Model for Organic Rice through Farmer Facilitation at Rojolele Studio in Delanggu Village. Rojolele rice development often faces problems in quality and operations. The closed-loop partnership model is one solution through the integration of the supply and value chain ecosystem from upstream to downstream, which mutually benefits all parties, including farmer groups. The Community Partnership Program by the Sebelas Maret University Service Team was carried out to facilitate increasing the competency and partnership of Sanggar Rojolele Delanggu farmers by implementing good agricultural practices (GAP) for organic rice products standardized by the Organic Certification Institute in Indonesia. Purposes of service: (1) increasing the hard skills & soft skills of farmers in developing organic Rojolele rice, (2) increasing productivity and farmer income, as long as (3) guaranteeing market certainty with competitive prices. The implementation method is through: (1) extension and training of farmers in the form of experiential learning through demonstration plots of organic Rojolele rice, (2) mentoring of low input Rojolele rice cultivation based on organic farming, and (3) facilitation of marketing networks for organic Rojolele rice harvest products with off taker PT. WSS Indonesia refers to quality standards according to SNI. The results of extension, training, and facilitation for farmers show an increase in farmers' knowledge and skills in implementing GAP for organic rice products and an increase in market absorption of products at higher prices.